Orthopedic case - Ferreira, Jorge Abreu; Martins, Cristiana; Peixoto, Paulo; Duarte, Filipe; Torres, José Samaniego; Santos, Jorge França (BIRTH AND GROWTH MEDICAL JOURNAL, 2018)
A previously healthy 12-month-old boy, was observed in the emergency department due to refusal to walk, initially diagnosed as transient synovitis of the hip. After one month, he is again observed due to the persistence of symptoms and fever. On objective examination he presented refusal to walk, reporting no difficulties in crawling. A conventional radiography showed lytic lesion on the medial condyle of the left femur and computed tomography (CT) revealed a probable Brodie abscess. Patient was referred to pediatric orthopedics consultation and then performed a magnetic ressonance that confirmed osteomyelitis with an intraosseous abscess. He was submitted to surgical drainage and four weeks of antibiotic therapy, with no sequelae after one year. Brodie’s abscess is a subtype of subacute osteomyelitis characterized by the formation of an intramedullary abscess, predominantly in the long bones. It is difficult to diagnose since the symptoms can be mild, mimicking several malignant or benign conditions. Radiology plays a key role in its identification. The treatment can be medical or medical-surgical, usually with a good prognosis.